1996
DOI: 10.1007/bf00144428
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus saprophyticus urinary tract infections: epidemiological data from Western Australia

Abstract: Epidemiological data from Western Australia regarding Staphylococcus saprophyticus urinary tract infections (UTIs) was collected over a 12 month period. Eighty-four percent of S. saprophyticus UTIs occurred in females 13-40 years of age and S. saprophyticus was the second most frequent cause of UTIs in this age group (15.2%) after Escherichia coli (70.8%). Although the monthly incidence fluctuated, no seasonality of S. saprophyticus UTIs could be demonstrated. The proportion of S. saprophyticus UTIs in pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
2
22
0
6
Order By: Relevance
“…saprophyticus is second only to E. coli as the most frequent causative organism of uncomplicated UTI in women. The vast majority of infections occur in young sexually active women 11,12 . It is referred to as "honeymooner's" UTI due to its association with intercourse.…”
Section: Introductionmentioning
confidence: 99%
“…saprophyticus is second only to E. coli as the most frequent causative organism of uncomplicated UTI in women. The vast majority of infections occur in young sexually active women 11,12 . It is referred to as "honeymooner's" UTI due to its association with intercourse.…”
Section: Introductionmentioning
confidence: 99%
“…The hormonal changes in pregnancy leads to decreased bladder tone, diminished peristalsis and dilatation of renal pelvis and ureter 16,17 It has been claimed that pregnancy produces physical obstruction in the female urinary tract and obstruction is one of the important risk factor for the development of the infection. 18,19 Diabetics are at higher risk of urinary tract infection due to the unfavourable metabolic changes such as elevated blood sugar levels, which suppress the immune system. In our study 10% UTI patients were diabetics, similar findings was found in study by Ramzan M.…”
Section: Resultsmentioning
confidence: 99%
“…El aislado de S. saprophyticus en urocultivos positivos (0,9%) en nuestra serie es ligeramente superior al 0,5% obtenido recientemente en el norte de Israel 20 . Sin embargo, los porcentajes de aislado en mujeres de 15 a 44 años en nuestro estudio (3%) son inferiores a los datos aportados por otros autores 1,5,18,19,21,22 , cuyos trabajos se realizaron entre 1978 y 1994, con estudios prospectivos de infecciones urinarias en mujeres jóvenes (de 13 a 40 años), con signos y/o síntomas de ITU en EE.UU., Canadá, Australia, Inglaterra y Suecia, con tasas de aislado entre el 7 y el 42% dependiendo, fundamentalmente, de la edad de la población elegida y del número de relaciones sexuales. Estas diferencias en la incidencia podrían deberse a las propias diferencias en la técnica e interpretación del urocultivo utilizado por diversos autores.…”
Section: Discussionunclassified
“…La edad media de nuestras pacientes infectadas (32,7 años) es superior a otros datos publicados 5,[20][21][22][23][24][25][26][27][28] ; probablemente, se deba a que, en nuestro país, cuanto mayor es la paciente, mayor número de ITU ha padecido y, por tanto, se realiza urocultivo con más frecuencia.…”
Section: Discussionunclassified
See 1 more Smart Citation